Pola pergerakan bekas-bekas murid sekolah menengah kebangsaan agama 1978-2004 - Zainuddin, Ahmad Marzuki; Ismail, Nik Ahmad Hisham; Nordin, Mohamad Sahari; Syed Abdullah Idid, Syed Arabi; Nik Abdul Rahman, Nik Suryani; Izhab, Zaleha (IIUM Press, 2009)
The purpose of this study is gather information on the status and the movement of the graduates of the Malayan National Religious Secondary School from 1979 until 2004. Specifically, the study surveyed the academic development, employment and economic status as well of self-efficacy and self esteem of these graduates. Simultaneously, the graduate assessments of the curriculum and academic facilities as well as non academic facilities of this school were also surveyed. 32 schools and 2021 respondents participated in the study. Results indicated majority of the respondent were still pursuing their tertiary education and believed that the school had helped mold their personality and self-esteem. though majority of the national religious school education system ought to be continued.